3D printing for sizing left atrial appendage closure device: head-to-head comparison with computed tomography and transoesophageal echocardiography. - Hell, Michaela M.; Yoo, In Seong; Achenbach, Stephan; Franke, Jörg; Blachutzik, Florian; Röther, Jens; Graf, Verena; Raaz-Schrauder, Dorette; Marwan, Mohamed; Schlundt, Christian (EuroIntervention, 2017)
AIMS Device sizing for LAA closure using transoesophageal echocardiography (TEE) can be challenging due to complex LAA anatomy. We investigated whether the use of 3D-printed left atrial appendage (LAA) models based on preprocedural computed tomography (CT) permits accurate device sizing. METHODS AND RESULTS Twenty-two (22) patients (73±8 years, 55% male) with atrial fibrillation requiring anticoagulation at high bleeding risk underwent LAA closure (WATCHMAN device). Preprocedurally, LAA was sized by TEE and third-generation dual-source CT. Based on CT, 3D printing models of LAA anatomy were created for simulation of device implantation. Device compression was assessed in a CT scan of the 3D model with the implanted device. Implantation was successful in all patients. Mean LAA ostium diameter based on TEE was 22±4 mm and based on CT 25±3 mm (p=0.014). Predicted device size based on simulated implantation in the 3D model was equal to the device finally implanted in 21/22 patients (95%). TEE would have undersized the device in 10/22 patients (45%). Device compression determined in the 3D-CT model corresponded closely with compression upon implantation (16±3% vs. 18±5%, r=0.622, p=0.003). CONCLUSIONS Patient-specific CT-based 3D printing models may assist device selection and prediction of device compression in the context of interventional LAA closur

Angiographic Findings and Revascularization Success in Patients With Acute Myocardial Infarction and Previous Coronary Bypass Grafting - Blachutzik, Florian; Achenbach, Stephan; Tröbs, Monique; Röther, Jens; Nef, Holger; Hamm, Christian; Schlundt, Christian (American Journal of Cardiology, 2016)
Current guidelines recommend invasive coronary angiography and interventional revascularization in ST-elevation and Non-ST-elevation myocardial infarction (STEMI and NSTEMI). The aim of this study was to analyze culprit lesions and percutaneous coronary intervention (PCI) success in patients with previous coronary artery bypass grafting (CABG). We analyzed the data of 121 consecutive patients in whom coronary angiography was performed in the setting of STEMI or NSTEMI and who had previous CABG. Coronary angiograms were reviewed, and clinical data were evaluated. The culprit vessel was identified by means of electrocardiographic findings, echocardiography, and coronary angiography. A bypass graft was the culprit vessel in 86% of patients with STEMI and 68% of patients with NSTEMI. Venous grafts were culprit vessels significantly more frequently than arterial grafts (81 of 260 venous grafts vs 4 of 65 arterial grafts, p <0.001). Attempted acute PCI was successful in 97% of native arteries (31 of 32 patients) but only in 81% of bypass grafts (68 of 84 patients, p = 0.031). Overall in-hospital mortality was 13% (STEMI: 25%, NSTEMI: 10%, p <0.001) and was significantly higher after failed acute PCI (6 of 11 patients; 55%) compared with successful acute PCI (7 of 110 patients; 6%; p = 0.006). In conclusion, the culprit lesion in patients with previous CABG who present with STEMI or NSTEMI is more often located in bypass grafts than in native arteries. Successful PCI is more likely in native arteries compared with bypass grafts.
EVALuna2:33683

Applicability and procedural success rate of bioresorbable-vascular scaffolds for percutaneous coronary intervention in an all-comer cohort of 383 consecutive patients - Schlundt, Christian; Achenbach, Stephan; Felten, Fabiola; Röther, Jens; Nef, Holger; Ludwig, Josef; Tröbs, Monique; Marwan, Mohamed (Acta Cardiologica, 2017)
Objectives The purpose of this study was to determine applicability and procedural success of bioresorbable vascular scaffolds (BVS) for percutaneous coronary intervention (PCI) in an all-comer cohort. Background BVS use in bifurcations and severely calcified lesions is not recommended, and a relatively large crossing profile may cause limitations. It is has never been studied how widely BVS can be applied in all-comer cohorts. Methods In 383 consecutive patients (acute coronary syndrome: 124, stable coronary disease 259), a BVS (Absorb) was used as first-line device unless any of the following contraindications were present: bifurcation with side branch >2.0 mm, reference diameter <2.5 mm or >4.0 mm, required device length <12 mm, in-stent stenosis, or contraindications to 6 months of DAPT. Patients and lesions were evaluated regarding suitability for BVS treatment, procedural success (successful BVS placement and residual stenosis <30%), and outcome. Results Of 588 lesions, 303 (52%) were unsuitable for BVS placement due to presence of a bifurcation (30% of unsuitable lesions), reference -diameter >4.0 mm (13%) or <2.5 mm (12%), contraindication to 6 months DAPT (13%), in-stent stenosis (14%), and desired device length <12 mm (4%). If BVS use was attempted, procedural success with a scaffold was 95% (271/285). Crossing failure occurred in 14 cases (5%), affected lesions were significantly more calcified. After a mean follow-up period of 259 days, definite/probable scaffold thrombosis occurred in 1.1% of patients. Conclusions Approximately one-half of lesions in an all-comer population can successfully be treated with BVS. Crossing failure is rare.
EVALuna2:33655

Bioresorbable vascular scaffold thrombosis in a consecutive cohort of 550 patients - Tröbs, Monique; Achenbach, Stephan; Röther, Jens; Klinghammer, Lutz; Schlundt, Christian (Catheterization and Cardiovascular Interventions, 2016)
OBJECTIVE: To determine the rate of bioresorbable vascular scaffold (BVS) thrombosis in a large, real-world population. BACKGROUND: There is some concern about device thrombosis after percutaneous coronary intervention (PCI) using BVS. No data have been published for PCI using both BVS and metal stents. METHODS: A cohort of 550 consecutive patients who underwent PCI for stable chest pain or acute coronary syndromes with implantation of at least one BVS (Absorb, Abbott Vascular) was systematically followed up by telephone interview and review of medical charts. Data on device thrombosis were retrospectively analyzed in relationship to clinical and angiographic characteristics. RESULTS: Follow-up was achieved in 533 patients (97%, median follow-up 233 days). A total of 964 BVS were implanted in 645 vessels. In addition, 234 metal stents were implanted in 149 patients, including "hybrid intervention" with the combined use of BVS and stents in the same artery in 122 patients. Documented were 15 definite, 1 probable, and 8 possible cases of device thrombosis (rate of definite/probable device thrombosis: 3.0%). Of these, 6 definite and 6 possible thromboses could be unambiguously attributed to BVS (1.1%), whereas a total of 11 definite, 1 probable, and 8 possible thromboses were potentially attributable to BVS (2.3%). Definite device thrombosis occurred in 7/122 patients with "hybrid intervention" (5.7%). CONCLUSIONS: In a large real-world cohort treated with BVS, the rate of scaffold thrombosis was higher than published for randomized trials. A high rate of thrombosis was observed after combined implantation of BVS and stents within one vessel. © 2016 Wiley Periodicals, Inc.
EVALuna2:33663

Comparison of Fractional Flow Reserve Based on Computational Fluid Dynamics Modeling Using Coronary Angiographic Vessel Morphology Versus Invasively Measured Fractional Flow Reserve - Tröbs, Monique; Achenbach, Stephan; Röther, Jens; Redel, Thomas; Scheuering, Michael; Winneberger, David; Klingenbeck, Klaus; Itu, Lucian; Passerini, Tiziano; Kamen, Ali; Sharma, Puneet; Comaniciu, Dorin; et al. (American Journal of Cardiology, 2016)
Invasive fractional flow reserve (FFRinvasive), although gold standard to identify hemodynamically relevant coronary stenoses, is time consuming and potentially associated with complications. We developed and evaluated a new approach to determine lesion-specific FFR on the basis of coronary anatomy as visualized by invasive coronary angiography (FFRangio): 100 coronary lesions (50% to 90% diameter stenosis) in 73 patients (48 men, 25 women; mean age 67 ± 9 years) were studied. On the basis of coronary angiograms acquired at rest from 2 views at angulations at least 30° apart, a PC-based computational fluid dynamics modeling software used personalized boundary conditions determined from 3-dimensional reconstructed angiography, heart rate, and blood pressure to derive FFRangio. The results were compared with FFRinvasive. Interobserver variability was determined in a subset of 25 narrowings. Twenty-nine of 100 coronary lesions were hemodynamically significant (FFRinvasive <=0.80). FFRangio identified these with an accuracy of 90%, sensitivity of 79%, specificity of 94%, positive predictive value of 85%, and negative predictive value of 92%. The area under the receiver operating characteristic curve was 0.93. Correlation between FFRinvasive (mean: 0.84 ± 0.11) and FFRangio (mean: 0.85 ± 0.12) was r = 0.85. Interobserver variability of FFRangio was low, with a correlation of r = 0.88. In conclusion, estimation of coronary FFR with PC-based computational fluid dynamics modeling on the basis of lesion morphology as determined by invasive angiography is possible with high diagnostic accuracy compared to invasive measurements.
EVALuna2:12050

Comparison of invasively measured FFR with FFR derived from coronary CT angiography for detection of lesion-specific ischemia: Results from a PC-based prototype algorithm - Röther, Jens; Moshage, Maximilian; Dey, Damini; Schwemmer, Chris; Tröbs, Monique; Blachutzik, Florian; Achenbach, Stephan; Schlundt, Christian; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: We evaluated the diagnostic accuracy of a novel prototype for on-site determination of CT-based FFR (cFFR) on a standard personal computer (PC) compared to invasively measured FFR in patients with suspected coronary artery disease. METHODS: A total of 91 vessels in 71 patients (mean age 65 ± 9 years) in whom coronary CT angiography had been performed due to suspicion of coronary artery disease, and who subsequently underwent invasive coronary angiography with FFR measurement were analyzed. For both cFFR and FFR, a threshold of ≤0.80 was used to indicate a hemodynamically relevant stenosis. The mean time needed to calculate cFFR was 12.4 ± 3.4 min. A very close correlation between cFFR and FFR could be shown (r = 0.85; p < 0.0001) with Bland-Altman analysis showing moderate agreement between FFR and cFFR with mild systematic overestimation of FFR values in CT (mean difference 0.0049, 95% limits of agreement ±2SD -0.007 to 0.008). Compared to FFR, the sensitivity of cFFR to detect hemodynamically significant lesions was 91% (19/21, 95% CI: 70%-99%), specificity was 96% (67/70, 95% CI: 88%-99%), positive predictive value 86% (95% CI: 65%-97%) and negative predictive value was 97% (95% CI: 90%-100%) with an accuracy of 93%. CONCLUSION: cFFR obtained using an on-site algorithm implemented on a standard PC shows high diagnostic accuracy to detect lesions causing ischemia as compared to FFR. Importantly, the time needed for analysis is short which may be useful for improving clinical workflow.
EVALuna2:36006

Comparison of standard- and high-dose intracoronary adenosine for the measurement of coronary fractional flow reserve (FFR) - Röther, Jens; Achenbach, Stephan; Tröbs, Monique; Blachutzik, Florian; Nef, Holger; Schlundt, Christian; Marwan, Mohamed (Clinical Research in Cardiology, 2016)
BACKGROUND: Measurement of fractional flow reserve (FFR) by intravenous infusion or intracoronary injection of adenosine is the reference method to determine the hemodynamic relevance of coronary artery stenoses. The goal of this prospective study was to compare standard (40 µg adenosine for the right and 80 µg for the left coronary artery) to high doses of intracoronary adenosine for FFR measurement. METHODS AND RESULTS: In 130 intermediate coronary artery stenoses, two sequential FFR measurements were performed with standard-dose intracoronary application of adenosine (40 µg for the right and 80 μg for the left coronary artery), followed by one FFR measurement with a bolus of 200 μg for the right and 400 μg for the left coronary artery. There was strong correlation (r = 0.97, p < 0.001) between FFR values determined with standard-dose adenosine (0.86 ± 0.08) versus high-dose adenosine (0.85 ± 0.08). High-dose adenosine did not yield FFR values ≤0.80 or ≤0.75 significantly more frequently than standard-dose adenosine. Patients reported more discomfort after high-dose adenosine application compared to standard-dose adenosine (p < 0.001). CONCLUSIONS: For FFR measurements with intracoronary adenosine injection, results achieved with doses of 40 µg adenosine for the right and 80 µg for the left coronary artery display no clinically relevant difference to doses of 200 and 400 µg, respectively.
EVALuna2:33662

CT-derived left ventricular global strain in aortic stenosis patients referred for transcatheter aortic valve implantation: a head-to-head comparison with echocardiography - Ammon, Fabian; Bittner, D.; Hell, M.; Schuhbaeck, A.; Röther, Jens; Feyrer, R.; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

CT-derived left ventricular global strain in aortic stenosis patients referred for transcatheter aortic valve replacement: a comparative study pre and post intervention - Bittner, D.; Hell, M.; Gitsioudis, Gitsios; Röther, Jens; Schuhbaeck, A.; Feyrer, R.; Arnold, M.; Achenbach, Stephan; Marwan, Mohamed (2017)
EVALuna2:36027

CT-derived left ventricular global strain in aortic valve stenosis patients: A comparative analysis pre and post transcatheter aortic valve implantation - Ammon, Fabian; Bittner, D.; Röther, Jens; Mekkhala, N.; Hell, M.; Schuhbaeck, A.; Gitsioudis, Gitsios; Feyrer, R.; Schlundt, Christian; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (Journal of Cardiovascular Computed Tomography, 2018)
INTRODUCTION: We assessed the potential of CT strain to detect changes in myocardial function in patients referred for TAVI pre and post intervention. PATIENTS AND METHODS: 25 consecutive patients with symptomatic aortic valve stenosis in whom TAVI had been performed were included in this analysis. Functional CT data sets acquired before and 3 to 6 months after TAVI were available. Multiphase reconstructions in increments of 10% of the cardiac cycle were rendered and transferred to a dedicated workstation (Ziostation2, Ziosoft Inc., Tokyo, Japan). For quantification of left ventricular strain, multiplanar reconstructions of the left ventricle in standard 4 chamber, 2 chamber as well as apical 3 chamber views were rendered. The perimeter of the left ventricle was traced dynamically through the cardiac cycle. Peak strain was calculated for each patient pre and post intervention. Furthermore, for quantification of 3-dimensional maximum principal strain, 2 volumetric regions of interests (VOI) were placed per each basal, mid and apical segment of the previously mentioned MPRs and peak maximal principal strain was calculated. Maximum principal strain as well as perimeter-derived longitudinal strain values in the three standard windows were averaged to obtain global strain. RESULTS: 25 patients were included in this analysis (mean age 78 ± 9 years, 13 males). Peak global maximum principal strain was significantly higher at follow-up compared to baseline (0.46 ± 0.19 vs. 0.59 ± 0.18, respectively, p = 0.001). Similarly global longitudinal strain derived by perimeter was significantly lower - implying better contraction - compared to baseline (-8.6% ± 2.8% vs. -9.8% ± 2.6%, respectively, p = 0.006). CONCLUSION: Using dedicated software, assessment of CT derived left ventricular strain is feasible. In patients treated with transcatheter aortic valve replacement, CT-derived parameters of global myocardial strain improve onshort-term follow-up.
EVALuna2:35994

Dual-axis rotational coronary angiography versus conventional coronary angiography: a randomized comparison - Hell, Michaela; Gilg, Melanie; Röther, Jens; Blachutzik, Florian; Achenbach, Stephan; Schlundt, Christian (Clinical Research in Cardiology, 2020)
Background: Dual-axis of rotational coronary angiography (RA), with one single cine acquisition during continuous C-arm motion along a pre-described path, is an alternative to conventional coronary angiography (CA). We assessed the performance of RA versus CA in a modern, experienced cath lab setting. Methods: Sixty-seven patients with suspected coronary artery disease undergoing invasive coronary angiography were randomized to CA (n = 35) or dual-axis RA (n = 32). CA was performed with four left and two right coronary artery acquisitions with manual contrast medium injection. In RA, one cine acquisition each was performed for the left (5 projections) and right coronary artery (3 projections) with a fixed amount of contrast medium applied by a power injector. In both groups, single cine acquisitions in additional angulations were performed to fully interpret the coronary system, if necessary. Procedural parameters and outcome were compared. Results: Mean age was 63 ± 12 years (64% males). Six additional projections were required in the RA group compared to 13 in the CA group (p = 0.173). Fluoroscopy duration (CA: 3 ± 3 min, RA: 3 ± 2 min, p = 0.748) and dose area product (CA: 1291 ± 761 µGym2, RA: 1476 ± 679 µGym2, p = 0.235) did not differ significantly between both groups. For CA, the amount of contrast medium (42 ± 13 vs. 46 ± 8 ml, p = 0.022) and procedure time (8 ± 5 vs. 11 ± 3 min, p < 0.001) were significantly lower. No major adverse event occurred during hospital stay. Conclusions: Dual-axis RA represents a feasible and safe alternative method to CA for obtaining coronary angiograms. However, no superiority was observed when performed by an experienced interventionalist with a modern system.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Coronary angiography; Coronary artery disease; Dual-axis rotational coronary angiography

Increased risk for vascular complications due to GP IIb/IIIa-antagonists in patients with cardiogenic shock supported by intraaortic balloon pump (IABP) - Röther, Jens; Tröbs, Monique; Schuhbäck, Annika; Ludwig, Josef; Achenbach, Stephan; Schlundt, Christian (Clinical Trials and Regulatory Science in Cardiology, 2015)
Background IABP is routinely used to support coronary blood flow and systemic circulation in patients with cardiogenic shock. Our aim was to explore the incidence of vascular complications associated with the use of IABP in this scenario and their influence on mortality. Methods Therefor we analysed 204 consecutive patients between 2002 and 2013 treated with IAPB in cardiogenic shock for vascular complications and mortality within 30 days after implantation of IAPB. Primary endpoints were severe bleeding (TIMI-definition: intracranial bleeding, loss of haemoglobin (Hb) > 5 g/dl or haematocrit (PCV) > 15%), vascular complications with therapeutic consequence (venous thrombosis, arterial embolism) and stroke. Results 80 (39%) patients died within 30 days after implantation of IABP. In 42 (21%) patients, vascular complications occurred: severe bleeding was present in 26 patients (62% of all complications), 13 (31%) patients suffered from venous thrombosis or arterial embolism and 3 (7%) patients from stroke. 25% of the patients who died had a vascular complication. The rate in patients who overcame cardiogenic shock was 17.7% (p = 0.22). Multivariate analyses showed treatment with Glycoprotein (GP) IIb/IIIa- inhibitors to be an independent risk factor for the occurrence of vascular complications (p = 0.04). Conclusion Vascular events with the use of IABP are common but in our study, not significantly associated with a higher mortality. Treatment with GP IIb/IIIa-antagonists is associated with a higher risk of vascular events.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiogenic shock; GP IIb/IIIa-antagonists; IABP; Vascular complications

Influence of image reconstruction parameters on diagnostic performance of on-site CT-derived FFR: Comparison with invasively measured FFR - Ammon, Fabian; Röther, Jens; Hell, M.; Schuhbaeck, A.; Achenbach, Stephan; Schlundt, Christian; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Leaflet thrombosis following transcatheter aortic valve implantation - Mekkhala, N.; Göller, Markus; Röther, Jens; Bittner, D.; Schuhbaeck, A.; Hell, M.; Muschiol, G.; Kolwelter, Julie; Feyrer, R.; Schlundt, Christian; Achenbach, Stephan; Arnold, M.; et al. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: Transcatheter aortic valve implantation (TAVI) is increasingly being offered to high-risk patients with symptomatic aortic valve stenosis. Recent reports have suggested a high incidence of subclinical leaflet thrombosis following bioprosthestic aortic valve replacement. We report the frequency and clinical presentation of leaflet thrombosis identified by cardiac CT in patients referred for follow-up contrast enhanced CT angiography following TAVI. METHODS: 91 consecutive patients referred for follow-up contrast-enhanced CT angiography following TAVI were screened for inclusion in this analysis. Out of these, 13 patients were excluded. All CT examinations were performed using a 2nd or a 3rd generation dual-source system (Somatom Definition Flash/Force, Forchheim, Germany). In all patients, retrospectively ECG-gated spiral acquisition with tube modulation was performed to allow for assessment of leaflet motion. All prostheses were analyzed for presence of leaflet thrombosis defined as hypo-attenuated leaflet thickening with or without leaflet restriction. Post-procedural antithrombotic regimen as well as symptom status was documented in all patients. RESULTS: 78 consecutive patients (35 males, 81 ± 4 years) were analyzed. TAVI had been performed in all patients (76 transfemoral access, 2 transapical access) with either balloon-expandable prostheses (4 Sapien XT, 64 Sapien 3) or self-expandable prostheses (5 SJM Portico, 5 Symetis Acurate). Follow-up CT angiography was performed at a median of 4 months following index procedure (Interquartile range 1 month). Leaflet thrombosis was detected in 18 patients (23%, 14 Sapien 3, 1 Sapien XT, 2 SJM Portico, 1 Symetis Acurate). In patients with leaflet thickening on CT, only 11% were on either oral anticoagulation or new oral anticoagulants versus 50% for patients with no leaflet thickening (p 0.002). In patients with leaflet thrombosis, 3 leaflets were affected in 5 patients, 2 leaflets in 5 patients and in 8 patient only 1 leaflet was affected. Clinical symptoms (angina, dyspnea or both) were reported in 2/18 patients with leaflet thrombosis (11%) and in both patients a significant increase of the mean echocardiographic gradient over the prosthesis was documented. The peak and mean echocardiographic gradients obtained at the day of CT examination was significantly higher in symptomatic patients versus asymptomatic patients (peak 46 ± 7 vs. 23 ± 11 mmHg, mean 29 ± 7 vs. 12 ± 6 mmHg, p = 0.01 and 0.002, respectively). Follow-up CT was available for 4 patients with complete resolution of the hypo-attenuated leaflet thickening following treatment. CONCLUSION: Leaflet thrombosis following TAVI is a relatively frequent finding in patients referred for contrast enhanced CT angiography following TAVI. In the majority of patients it follows a subclinical course and is substantially more frequent in individuals who are not on oral anticoagulation. However, in patients with relevant increase in prosthetic gradients, symptomatic presentations are possible.
EVALuna2:33589

Major coronary evaginations following implantation of bioresorbable vascular scaffolds: clinical and OCT characteristics - Blachutzik, F.; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, R.; Weissner, M.; Schlundt, Christian; Marwan, Mohamed (2017)
EVALuna2:36025

Major coronary evaginations following implantation of bioresorbable vascular scaffolds - Clinical and OCT characteristics - Blachutzik, Florian; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, Reinhard; Nef, Holger; Weissner, Melissa; Schlundt, Christian; Marwan, Mohamed (Cardiovascular Revascularization Medicine, 2019)
Background: Coronary evaginations can occur after implantation of bioresorbable vascular scaffolds (BRS) and may be associated with scaffold thrombosis. Aim of this study was to clarify the clinical manifestation, extent and time course of coronary artery remodeling in vessel segments that develop angiographically detectable evaginations following BRS implantation through optical coherence tomography (OCT) analysis.
CRIS-Team WoS Importer:2019-06-18

Multispectral Optoacoustic Tomography for Assessment of Crohn's Disease Activity - Knieling, Ferdinand; Neufert, Clemens; Hartmann, Arndt; Claussen, Jing; Urich, Alexander; Egger, Cornelia; Vetter, Marcel; Fischer, Sarah; Pfeifer, Lukas; Hagel, Alexander; Kielisch, Christian; Görtz, Rüdiger; et al. (New England Journal of Medicine, 2017)
EVALuna2:33821

Optical coherence tomography: influence of contrast concentration on image quality and diagnostic confidence - Blachutzik, Florian; Achenbach, Stephan; Nef, Holger; Hamm, Christian; Dorr, Oliver; Boeder, Niklas; Tröbs, Monique; Schneider, Reinhard; Röther, Jens; Schlundt, Christian; Marwan, Mohamed (Heart and Vessels, 2017)
OCT requires intracoronary injection of contrast agent to remove blood from the coronary lumen during data acquisition, which is a possible limitation of this method. Aim of this study was to analyze the influence of iodine concentration on image quality and diagnostic certainty of optical coherence tomography (OCT). OCT sequences acquired using contrast agent with a reduced concentration of 150 mg iodine/ml and a standard concentration of 350 mg iodine/ml were analyzed. Cross-sectional images with a spacing of 10 mm were evaluated regarding image quality and diagnostic confidence. A total of 67 OCT sequences acquired in 24 patients were analyzed. 31 sequences were acquired using contrast agent with a concentration of 150 mg iodine/ml and 36 sequences with a concentration of 350 mg iodine/ml. The percentage of remaining blood streaks in the cross sections was significantly lower for 350 mg iodine/ml compared to 150 mg iodine/ml (19 ± 21 vs. 34 ± 26%, p = 0.013). Contrast with 350 mg iodine/ml showed a significantly higher percentage of completely flushed pullback length as compared to 150 mg iodine/ml (78 ± 24 vs. 58 ± 27%, p = 0.004). Diagnostic certainty was significantly higher for 350 mg iodine/ml than for 150 mg iodine/ml (Likert scale average 1.4 ± 0.7 vs. 2.1 ± 1.2, p < 0.001; Likert scale: 1 = absolutely confident, 2 = confident with slight doubts, 3 = doubtful/not confident, 4 = non-diagnostic). Regarding image quality and diagnostic certainty, contrast agent with a concentration of 350 mg iodine/ml is superior to 150 mg iodine/ml.
EVALuna2:33638

Overlapping implantation of bioresorbable novolimus-eluting scaffolds: an observational optical coherence tomography study - Blachutzik, Florian; Boeder, Niklas; Wiebe, Jens; Mattesini, Alessio; Doerr, Oliver; Most, Astrid; Bauer, Timm; Tröbs, Monique; Röther, Jens; Schlundt, Christian; Achenbach, Stephan; Hamm, Christian; et al. (Heart and Vessels, 2017)
Overlapping implantation of bioresorbable vascular scaffolds is frequently necessary, but its influence on vessel and scaffold structure has not been thoroughly analyzed previously. The aim of this study was to analyze the acute effects of overlapping implantation on BRS as determined by optical coherence tomography (OCT). A total of 38 patients with de novo coronary artery stenoses who underwent OCT in the context of implantation of novolimus-eluting BRS (DESolve, Elixir Medical Corporation, Sunnyvale, California, USA) were investigated. In 15 patients, overlapping implantation of two BRS was performed, while 23 patients with implantation of one single BRS served as the control group. OCT data were retrospectively analyzed regarding acute scaffold implantation results. There were no significant differences between the overlap and control group in terms of residual in-scaffold area stenosis, scaffold area, mean or minimal lumen area, eccentricity index, incomplete scaffold apposition area or malapposition. While strut fracture was slightly more frequent in BRS with overlap its incidence was low overall. In patients with overlapping BRS, overlap segments did not display smaller lumen areas than segments without overlap (mean lumen area overlap: 8.16 ± 2.97 mm2vs. no overlap: 7.70 ± 2.55 mm2; p = 0.71; minimal lumen area overlap: 6.83 ± 2.71 mm2vs. no overlap: 6.17 ± 2.58 mm2; p = 0.37). Acute mechanical performance of novolimus-eluting BRS is not impaired by overlapping implantation. It can be assumed that vessel expansion compensates for the double scaffold layer in the overlap area resulting in a similar lumen area in overlap areas and in those with a single strut layer.
EVALuna2:33634

Percutaneous coronary intervention of unprotected left main stenoses - Procedural data and outcome depending on SYNTAX I Score - Blachutzik, Florian; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, Reinhard; Schlundt, Christian; Marwan, Mohamed (Cardiovascular Revascularization Medicine, 2018)
BACKGROUND: We hypothesized that SYNTAX I score is a predictor for procedure complexity in left main PCI. Procedure complexity, duration and contrast load may contribute to adverse outcome of complex left main percutaneous coronary intervention (PCI). METHODS: In 105 consecutive patients who underwent PCI of unprotected left main coronary artery stenoses between 2014 and 2016, clinical parameters as well as PCI characteristics and follow-up data were analyzed. RESULTS: The mean SYNTAX I score was 29 ± 12, with 66 patients having a SYNTAX I score ≤ 32 and 39 patients a SYNTAX I score > 32. In patients with high SYNTAX I score vs. low-to-intermediate SYNTAX I score, single stent techniques were performed significantly less frequently (18% vs. 68%; p < 0.001), while Crush (44% vs. 5%; p < 0.001) and Culotte techniques (20% vs. 5%; p = 0.003) were performed significantly more frequently. Procedural success was achieved in all 105 cases without periprocedural mortality. During follow up, repeat PCI was necessary significantly more frequently in patients with high compared to patients with low-to-intermediate SYNTAX I score (34% vs.13%; p = 0.003). Nevertheless, overall mortality did not differ between patients with high vs. low-to-intermediate SYNTAX I score (20% vs. 18%). CONCLUSIONS: PCI strategies for the treatment of left main coronary artery stenoses get significantly more complex with increasing SYNTAX I scores. While this translates into a significantly longer procedure duration and contrast load, short-term outcome seems not to be influenced by the SYNTAX I score.
EVALuna2:213082

Post-dilatation after implantation of bioresorbable everolimus- and novolimus-eluting scaffolds: an observational optical coherence tomography study of acute mechanical effects - Blachutzik, Florian; Boeder, Niklas; Wiebe, Jens; Mattesini, Alessio; Doerr, Oliver; Most, Astrid; Bauer, Timm; Röther, Jens; Tröbs, Monique; Schlundt, Christian; Achenbach, Stephan; Hamm, Christian W.; et al. (Clinical Research in Cardiology, 2017)
OBJECTIVES: The objective was to investigate the acute mechanical effects of post-dilatation on bioresorbable scaffolds (BRS) as determined by optical coherence tomography (OCT). BACKGROUND: Post-dilatation with high-pressure balloons is regarded as a key component of BRS implantation for treatment of coronary artery stenoses. However, the impact of post-dilatation on BRS in vivo has not been thoroughly investigated. METHODS: OCT was performed after the implantation procedure of 51 everolimus-eluting or novolimus-eluting polylactic acid-based BRS with (n = 27) or without non-compliant balloon post-dilatation (n = 24). The number of malapposed struts, strut fractures, edge dissections, residual in-scaffold area stenosis, and incomplete scaffold apposition area was analyzed over the complete length of each BRS with a spacing of 1 mm. RESULTS: OCT revealed a significantly lower incomplete scaffold apposition area if post-dilatation was performed (0.16 ± 0.49 mm2with post-dilatation vs. 2.65 ± 2.78 mm2without post-dilatation, p < 0.001), as well as a significantly lower absolute number of malapposed struts (1 ± 2 with post-dilatation vs. 13 ± 13 without post-dilatation, p < 0.001). No significant differences regarding residual in-scaffold area stenosis, strut fracture, edge dissection, symmetry index, or eccentricity index were observed in patients with vs. without post-dilatation. CONCLUSION: Post-dilatation of BRS with non-compliant balloons significantly reduces the number of malapposed struts and incomplete scaffold apposition area without inducing higher rates of edge dissection or strut fracture.
EVALuna2:33645

Postdilatation after implantation of bioresorbable everolimus- and novolimus-eluting scaffolds: an observational optical coherence tomography study on acute mechanistic effects - Blachutzik, F.; Boeder, N.; Wiebe, J.; Mattesini, A.; Doerr, O.; Most, A.; Bauer, T.; Koepp, T.; Tröbs, Monique; Röther, Jens; Schlundt, Christian; Achenbach, Stephan; et al. (2016)
EVALuna2:33685

Predictors of Technical Failure in Transradial Coronary Angiography and Intervention - Tröbs, Monique; Achenbach, Stephan; Plank, Pia Maria; Röther, Jens; Klinghammer, Lutz; Blachutzik, Florian; Schlundt, Christian; Marwan, Mohamed (American Journal of Cardiology, 2017)
Transradial access for coronary angiography and intervention is preferred over the femoral approach but can be technically challenging. Identification of predictors of transradial access failure is important, especially in the context of acute coronary syndromes. We therefore retrospectively analyzed 13,095 consecutive patients (66 ± 12 years, 64% male) in whom transradial access was attempted for coronary angiography or intervention to identify predictors of transradial access failure. Angiograms and patient files were systematically reviewed to analyze patient characteristics associated with failure. Transradial access failure rate was 6.8% (909 of 13,095). Patients with transradial access failure were more frequently female (9.5% vs 5.5%; p <0.001), significantly older (68 ± 12 vs 66 ± 12 years, p <0.001), and had a smaller body surface area (1.89 ± 0.21 vs 1.94 ± 0.2 m2; p <0.001). Transradial failure was not significantly more frequent in ST-elevation myocardial infarction versus other patients (8.1% vs 6.9%, p = 0.195). After multivariable adjustment, only female sex (odds ratio [OR] 1.44, p <0.001), higher patient age (OR 1.01/year, p = 0.002), and lower height (OR 0.98/cm, p = 0.004) independently predicted transradial access failure. In conclusion, female sex, higher age, and smaller height independently predict transradial access failure in coronary angiography and intervention. Failure rate in ST-elevation myocardial infarction is not significantly increased.
EVALuna2:33605

Treatment and outcome of coronary artery perforations using a dual guiding catheter technique - Röther, Jens; Tröbs, Monique; Ludwig, Josef; Achenbach, Susanne; Schlundt, Christian (International Journal of Cardiology, 2015)
To evaluate the success rate and outcome of coronary artery perforation treatment using a dual guiding catheter technique.Coronary artery perforation is a rare but severe complication during percutaneous coronary intervention (PCI) with high mortality. The use of a second guiding catheter is a helpful technique to minimize hemorrhage through the perforation during interventional repair.We screened all patients between March 2004 and December 2014 who underwent PCI in our department for the occurrence of peri-interventional coronary perforation that was treated using a dual catheter technique. Patient and lesion characteristics as well as outcome were determined.We identified 8 patients who experienced coronary artery perforations (Ellis grade III) during coronary intervention and were treated using a dual guiding catheter approach. The procedure was technically successful (placement of covered stent and sealing of perforation) in 6 patients. Pericardiocentesis was required in 3 patients (38%). Total mortality was 12% (n=1). No coronary or peripheral vascular access complication occurred due to the use of a second guiding catheter.We suggest that the dual guiding catheter technique is a useful and alternative approach to treat severe Ellis grade III coronary artery perforations that occur in the context of percutaneous coronary interventions.
EVALuna2:12076